2016
DOI: 10.17146/aij.2016.511
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of AP1000 Passive Systems during Direct Vessel Injection (DVI) Line Break

Abstract: Generation II Nuclear Power Plants (NPPs) have a design weakness as shown by the Fukushima accident. Therefore, Generation III+ NPPs are developed with focus on improvements of fuel technology and thermal efficiency, standardized design, and the use of passive safety system. One type of Generation III+ NPP is the AP1000 that is a pressurized water reactor (PWR) type that has received the final design acceptance from US-NRC and is already under construction at several sites in China as of 2015. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Also, the highest peak of pressure is similar to the Design Control Document (DCD) result for long-term analysis. Meanwhile, Ekariansyah and Widodo [13] evaluated the PXS performance to mitigate Direct vessel injection line break (DVI-LB) using RELAP5/SCDAP/Mod 3.4. It is confirmed that the failure of DVI lines can be anticipated using injected coolant, which is operated based on a passive system so that the reactor core is always safe.…”
Section: Esfta Verificationmentioning
confidence: 99%
“…Also, the highest peak of pressure is similar to the Design Control Document (DCD) result for long-term analysis. Meanwhile, Ekariansyah and Widodo [13] evaluated the PXS performance to mitigate Direct vessel injection line break (DVI-LB) using RELAP5/SCDAP/Mod 3.4. It is confirmed that the failure of DVI lines can be anticipated using injected coolant, which is operated based on a passive system so that the reactor core is always safe.…”
Section: Esfta Verificationmentioning
confidence: 99%
“…Until now, any safety analysis conducted has been performed using deterministic best estimate approach only when the model nodalization was developed as close as possible with the real nuclear power plant and the results to evaluate the safety criteria also were compared with the best estimate simulation using different code. Such best estimate analyses can be found in several scientific papers related to the AP1000 nuclear power plant [16,17] without considering uncertainty arising during modelling and simulation. The ATLAS test facility is selected due to the availability of the experimental results and related analysis is needed to validate the best estimate simulation.…”
Section: Introductionmentioning
confidence: 99%